Pusong bato - Escobar, Martika Ramirez 1992-; Campos, Patrick F.; University of the Philippines. College of Mass Communication (2014)
"Pusong Bato is about Cinta dela Cruz, a middle-aged faded actress who tries to relive and remember her glorious days as a movie star in the '70s. She does this by watching films at home everyday until one day, during an earthquake, something breaks into her window and wakes her up from her Hollywood dream. Using post-colonial studies as the bedrock of the film, Pusong Bato becomes a satirical piece on the colonial influence on Philippine culture."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Satirical films; Imperialism